Mobility with a lower limb prosthesis: experiences of users with high levels of functional ability. Issue 13 (19th June 2022) - Morgan, Sara J.; Liljenquist, Kendra S.; Kajlich, Andre; Gailey, Robert S.; Amtmann, Dagmar; Hafner, Brian J.
Abstract: Purpose: The Prosthetic Limb Users Survey of Mobility (PLUS-M) is a self-report item bank designed to measure the abilities with which people with lower limb amputation perform physical activities. Although PLUS-M includes items that span a range of mobility, additional items are needed to accurately measure mobility of highly active prosthesis users, such as athletes and service members with lower limb amputation. The aim of this study was to understand mobility in highly active lower limb prosthesis users to inform the development of new items for the PLUS-M item bank. Methods: Focus groups were conducted with active, lower limb prosthesis users from across the USA. In-person and online focus groups were conducted by a trained facilitator using a semi-structured guide. Focus group transcripts were reviewed and coded by two researchers. Thematic analysis was used to identify important experiences across participants. Results: Twenty-nine participants took part in four focus groups. Three resultant themes were identified: mobility after amputation, mobility characteristics, and healthcare providers and systems. Conclusions: Identified themes inform clinician and researcher understanding of mobility in highly active lower limb prosthesis users. The results of this study will be used to inform development of high-activity items for the PLUS-M item bank. Implications for rehabilitation: Participants described engagement in high-level activities as a learning process that included elements such as equipment challenges and modifications, pain and injury, and the need to trust the prosthetic limb. Participants with lower limb amputation who use prostheses identified mobility characteristics, such as postural changes, terrain, and obstacles, that influenced their ability to perform high-level activities. High-level mobility characteristics identified in these focus groups can be integrated into a revised version of the Prosthetic Limb Users Survey of Mobility to assess mobility in active adults and athletes with amputation. Rehabilitation professionals play an important role in facilitating access to specialized prosthetic components and training that can help patients achieve their mobility goals and potential.